Prefrontal direct current stimulation modulates resting EEG and event-related potentials in healthy subjects: A standardized low resolution tomography (sLORETA) study - Keeser, D.; Padberg, F.; Reisinger, E.; Pogarell, O.; Kirsch, V.; Palm, U.; Karch, S.; Möller, H.-J.; Nitsche, M.A.; Mulert, C. (NeuroImage (Orlando, Fla.), 2011)
Prefrontal transcranial direct current stimulation (tDCS) with the anode placed on the left dorsolateral prefrontal cortex (DLPFC) has been reported to enhance working memory in healthy subjects and to improve mood in major depression. However, its putative antidepressant, cognitive and behavior action is not well understood. Here, we evaluated the distribution of neuronal electrical activity changes after anodal tDCS of the left DLPFC and cathodal tDCS of the right supraorbital region using spectral power analysis and standardized low resolution tomography (sLORETA). Ten healthy subjects underwent real and sham tDCS on separate days in a double-blind, placebo-controlled cross-over trial. Anodal tDCS was applied for 20min at 2mA intensity over the left DLPFC, while the cathode was positioned over the contralateral supraorbital region. After tDCS, EEG was recorded during an eyes-closed resting state followed by a working memory (n-back) task. Statistical non-parametric mapping showed reduced left frontal delta activity in the real tDCS condition. Specifically, a significant reduction of mean current densities (sLORETA) for the delta band was detected in the left subgenual PFC, the anterior cingulate and in the left medial frontal gyrus. Moreover, the effect was strongest for the first 5min (p<0.01). The following n-back task revealed a positive impact of prefrontal tDCS on error rate, accuracy and reaction time. This was accompanied by increased P2- and P3- event-related potentials (ERP) component-amplitudes for the 2-back condition at the electrode Fz. A source localization using sLORETA for the time window 250–450ms showed enhanced activity in the left parahippocampal gyrus for the 2-back condition. These results suggest that anodal tDCS of the left DLPFC and/or cathodal tDCS of the contralateral supraorbital region may modulate regional electrical activity in the prefrontal and anterior cingulate cortex in addition to improving working memory performance. ► Prefrontal tDCS (tDCS) reduces slow-wave activity. ► Prefrontal RtDCS tend to increase high-frequency activity. ► Prefrontal rtDCS improves performance (errors, accuracy) in a working memory task (n-back). ► This is accompanied by P2- and P3-amplitude increases. ► And by an increased left parahippocampal activity (sLORETA).